Macrophage interactions with collecting duct epithelial cells are capable of driving tubulointerstitial inflammation and fibrosis in immunoglobulin A nephropathy. Issue 11 (23rd August 2020) - Pawluczyk, Izabella Z A; Soares, Maria S F; Barratt, William A; Brown, Jeremy R; Bhachu, Jasraj S; Selvaskandan, Haresh; Zeng, Yiqing; Sarania, Rishi; Molyneux, Karen; Roberts, Ian S D; Barratt, Jonathan
Abstract: Background: Tubulointerstitial fibrosis is a powerful predictor of future progression inimmunoglobulin A (IgA) nephropathy (IgAN). Proximal tubular epithelial cells (PTECs), in concert with infiltrating macrophages, are regarded as the agents provocateurs for driving this fibrotic process. However, evidence is now emerging for a contributory role of the distal nephron. The aim of this study was to examine the potential influence of macrophages on collecting duct epithelial cells (CDECs) and their combined role in the progression of IgAN. Methods: CDECs were cultured with macrophage-conditioned media (MCM) generated from human monocyte cell lines U937 and THP-1 stimulated with or without 100 μg/mL galactose-deficient IgA1. CDECs were analysed for evidence of inflammation and fibrosis. Results: Staining of IgAN biopsies for CD68 + macrophages revealed the presence of macrophages juxtaposed to collecting ducts and within their lumina. CDEC exposed to MCM from IgA1-stimulated THP-1 cells (THP-1-IgA-MCM) exhibited markedly increased expression of neutrophil-associated gelatinase (NGAL) and proinflammatory cytokinesinterleukin (IL)-1β, tumour necrosis factor-α, IL-6 and IL-8 compared with MCM from non-IgA-stimulated THP-1 cells (THP-1-MCM). U937-IgA-MCM increased fibronectin levels and reduced E-cadherinmRNA expression. THP-1-IgA-MCM-derived exosomes induced similar increases in NGAL and cytokine expression while in cross-over experiments exosomes extracted from IL-1β-exposed CDEC induced IL-1β and IL-6 mRNA expression in both sets of macrophages. MiRnome analysis revealed that microRNA (miR)-146a, -155 and -200b exhibited a >2-fold increase in expression in CDEC treated with THP-1-IgA-MCM compared with THP-1-MCM. Enforced miR-146a suppression further enhanced NGAL expression, while ectopic miR-146a over-expression downregulated it. NGAL mRNA and miR-146a were upregulated in the biopsies of patients with progressive IgAN compared with non-progressive IgAN. Conclusions: Taken together, these data suggest that CDEC–macrophage interactions potentially contribute to the tubulointerstitial fibrosis characteristic of progressive IgAN.